Hubungan Good Corporate Governance Terhadap Kinerja Perusahaan : Studi Kasus Pada BPS Kabupaten Jombang: Studi Kasus Pada BPS Kabupaten Jombang - alfiary fradana mellenio (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research was conducted at Badan Pusat Statistik (BPS) of Jombang Regency, where according to the Statistical Law No. 16 of 1997, Badan Pusat Statistik (BPS) is tasked with organizing integrated national statistics in order to realize a reliable, effective and efficient National Statistics System. To carry out tasks and functions in the regions, BPS establishes BPS Representative Offices in each Province and Regency/City which are vertical agencies. This research is a descriptive qualitative research with a case study approach. This study aims to analyze the effect of Good Corporate Governance (CGG) on company performance. The principles of good corporate governance include principles that are implemented in the programs implemented by BPS, such as surveys and data presentation. To meet these basic statistical needs, BPS has carried out the 2020 Population Census as well as several surveys and data collection including Survey Industri Sosial Ekonomi Nasional (SUSENAS), Survey Angkatan Kerja Nasional (SAKERNAS), Large/Medium Industry Survey, Construction Survey, Tourism Services Sector Survey, Forestry Company Survey, Plantation Company Survey, Tile Food Crops Survey, KSA and other surveys. The results showed that the implementation of GCG had an effect on the company's performance. Higher corporate governance can be measured by the perception of the corporate governance index, the higher the company's compliance and result in good company performance. The full implementation of GCG principles makes the implementation of the BPS program more focused and focused.